2012
DOI: 10.1038/onc.2011.603
|View full text |Cite
|
Sign up to set email alerts
|

Diversity within the pRb pathway: is there a code of conduct?

Abstract: The failure of cell proliferation to be properly regulated is a hallmark of tumourigenesis. The retinoblastoma protein (pRb) pathway represents a key component in the regulation of the cell cycle and tumour suppression. Recent findings have revealed new levels of complexity reflecting a repertoire of post-translational modifications that occur on pRb together with its key effector E2F-1. Here we provide an overview of the modifications and consider the possibility of a 'code' that endows pRb with the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 92 publications
2
98
0
Order By: Relevance
“…23 In addition, methylation of RB have been shown to affect its function. 25 Therefore, we intended to determine whether JMJD3 interacted with RB. First, we examined the relationship between JMJD3 and RB by using the co-immunoprecipitation (CoIP) assay, and the results showed that the ectopically expressed His-JMJD3 and Flag-RB in HEK-293T cells (Figure 4a), as well as the endogenous JMJD3 and RB in WI38 cells (Figure 4b), were co-precipitated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…23 In addition, methylation of RB have been shown to affect its function. 25 Therefore, we intended to determine whether JMJD3 interacted with RB. First, we examined the relationship between JMJD3 and RB by using the co-immunoprecipitation (CoIP) assay, and the results showed that the ectopically expressed His-JMJD3 and Flag-RB in HEK-293T cells (Figure 4a), as well as the endogenous JMJD3 and RB in WI38 cells (Figure 4b), were co-precipitated.…”
Section: Resultsmentioning
confidence: 99%
“…25 The truncated peptide RB(659-840) shown to interact with JMJD3 described above comprises the K810 residue, and this encouraged us to speculate that K810 may be the site JMJD3 demethylates the RB protein. Set7/9 is a methyltransferase reported to methylate the K810 and K873 sites at the C-terminal region of RB.…”
Section: Rb As Shown In Supplementarymentioning
confidence: 99%
See 2 more Smart Citations
“…The idea that pRB's binding activity is tailored by phosphorylation is only part of the story. Evidence that pRB is both acetylated and methylated in specific contexts (Chan et al 2001;Nguyen et al 2004;Leduc et al 2006;Munro et al 2010;Saddic et al 2010), evidence of interplay between different post-translational modifications (Carr et al 2011;Macdonald and Dick 2012;Munro et al 2012;Kim et al 2015), and evidence that pRB interacts with specific partners in response to cellular cues (MacLellan et al 2000;Miyake et al 2000;Dick and Dyson 2003;Nguyen et al 2004;Carr et al 2014) all suggest additional levels of diversity. Collectively, these observations raise several intriguing possibilities: (1) There may be multiple pools of pRB that perform different functions.…”
Section: How Large Is the Prb Interactome And How Is It Organized?mentioning
confidence: 99%